2013
DOI: 10.1017/s0950268813000253
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the clinical and economic burden of healthcare-associated infections during hospitalization for surgery in France

Abstract: SUMMARYOver 4 million patients suffer nosocomial infections annually in the European Union. This study aimed to estimate the healthcare burden associated with healthcare-associated infections (HAIs) following surgery in France, and explore the potential impact of infection control strategies and interventions on the clinical and economic burden of disease. Data on the frequency of HAIs were gathered from the 2010 Programme de Médicalisation des Systèmes d'Information (PMSI), and cost data were taken from the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 11 publications
2
44
1
2
Order By: Relevance
“…Moreover, PJI incurs considerable health care costs. [1][2][3] Therefore, multiple strategies including antibiotic prophylaxis, body exhaust systems, and laminar airflow systems have been developed to reduce the incidence of PJI. Studies have also identified modifiable risk factors ORIGINAL ARTICLE aureus was the most common causative organism.…”
Section: Implications For Clinical Practice or Policymentioning
confidence: 99%
“…Moreover, PJI incurs considerable health care costs. [1][2][3] Therefore, multiple strategies including antibiotic prophylaxis, body exhaust systems, and laminar airflow systems have been developed to reduce the incidence of PJI. Studies have also identified modifiable risk factors ORIGINAL ARTICLE aureus was the most common causative organism.…”
Section: Implications For Clinical Practice or Policymentioning
confidence: 99%
“…The International Nosocomial Infection Control Consortium, a voluntary multicentre collaborative that includes hospitals from many low‐income countries, noted that SSI rates were higher for more than half of the surgical procedures in their hospitals compared with those published by the US Centers for Disease Control and Prevention National Healthcare Safety Network. In addition, the clinical and economic burden of SSIs is well documented, regardless of geography. SSIs are associated with prolonged hospital stay, more readmissions, additional surgical procedures, prolonged antibiotic use and antimicrobial resistance, and increased health resource utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Their use, as a medico-administrative and an economic database, respectively, allowed for carrying out previous medico-economic analyses [17]. The French College of Health Economists recommended using this medico-administrative database for health economic evaluations [18].…”
Section: Methodsmentioning
confidence: 99%